Computer-Aided Rehabilitation for the Carpal Tunnel Syndrome using Exergames - Pachoulakis, Ioannis; Tsilidi, Diana; Analyti, Anastasia (European Journal of Applied Sciences, 2018)
Carpal tunnel syndrome (CTS) has reached epidemic proportions as the surgical release of the transverse carpal ligament is included in the top ten most common operations, which significantly affects health care costs. Additional costs to consider include time off work, lost wages, and diminished workplace productivity. Non-surgical management of CTS such as splinting, non-steroidal anti-inflammatory medication, steroid injections and ergonomic modification of the work habits can help in early cases, but can be ineffective in more advanced cases, often leading to recommendation for surgical treatment. It is possible to attain meaningful physiotherapy results through interesting and engaging computer-based games which provide the motivation to continue therapy at home, even away from direct therapist supervision. Motivation and immersion in the game scenario also helps patients forget that they are performing exercises as a part of their therapy. Accordingly, we present a Unity3D Fly-A-Plane game, the scenario of which combines CTS-specific physiotherapy exercises in a natural game scenario to fly an airplane through a sequence of hoops in the sky. The game employs the Leap Motion sensor, whose detailed wrist and hand (including fingers) tracking abilities make it an excellent hardware platform for rehabilitation oriented exercises intended for patients suffering from CTS.